A cosmopolitan return to nature: how combining aesthetization and moralization processes expresses distinction in food consumption. Issue 4 (4th July 2017) - Emontspool, Julie; Georgi, Carina
ABSTRACT: This article investigates how foodies' adoption of New Nordic Food enables them to combine aesthetic and moral cosmopolitanism ideals. It demonstrates that consumers integrate aesthetic and moral cosmopolitan discourses through two complementary processes: the re-aesthetization of nature and the re-moralization of the exotic. These processes combine in a cosmopolitan interest for one of the last unexplored foreign contexts: nature. The findings of this article contribute to existing research by showing that moral cosmopolitanism reflects a more individualized and less engaged form of consumption than ethical consumption. They illustrate how urban consumers perform distinction in contexts where nature is the most exotic unexplored context, highlighting further the reterritorialization of global cosmopolitan consumption, where food trends can only be consumed authentically in their context of origin. Finally, this article shows how moral cosmopolitanism can support consumers who acknowledge the need for ethical consumption yet struggle with its adoption.